1999
DOI: 10.1034/j.1399-6576.1999.430807.x
|View full text |Cite
|
Sign up to set email alerts
|

Modified natural and synthetically reconstituted surfactant therapies for acute lung injury caused by endotoxin in rats

Abstract: In this acute lung injury model, the effects of replacement therapy with surfactant consisting of synthetic phospholipids, SP-B and SP-C, were the same as those observed with MNS. These results warrant development of surfactant substitutes based on natural SP-B and SP-C, and synthetic phospholipids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Tashiro and colleagues [45] demonstrated in rat model of sepsisinduced adult respiratory distress syndrome (ARDS) that an artificial surfactant reconstituted with SP-B and SP-C was as effective as porcine modified natural surfactant in restoring oxygenation and normalising pressure-volume curves. Similarly, Walther et al [35] demonstrated that beractant spiked with supplemental SP-B and SP-C was superior to unmodified beractant in restoring oxygenation and normalised pressure-volume relationships in another rat surfactant wash-out model.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Tashiro and colleagues [45] demonstrated in rat model of sepsisinduced adult respiratory distress syndrome (ARDS) that an artificial surfactant reconstituted with SP-B and SP-C was as effective as porcine modified natural surfactant in restoring oxygenation and normalising pressure-volume curves. Similarly, Walther et al [35] demonstrated that beractant spiked with supplemental SP-B and SP-C was superior to unmodified beractant in restoring oxygenation and normalised pressure-volume relationships in another rat surfactant wash-out model.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Moreover, Tashiro and colleagues employed peak inspiratory pressures of 2.5 kPa and a PEEP of 0.75 kPa in the rat, without any evidence of pulmonary tissue damage [14]. 646 C. Hofstetter et al…”
Section: Discussionmentioning
confidence: 99%
“…In the rat, endobronchial or intrapulmonary administration of therapeutical agents has regularly been performed either by inhalation of aerosols during spontaneous breathing or by direct instillation of liquid preparations, respectively [11][12][13][14][15]. However, intratracheal instillation is not a physiological route of delivery and results from those investigations may not be transferable to the general clinical situation.…”
mentioning
confidence: 99%
“…Several different agents can be classified among this group including bronchospasmolytics [67][68][69], trypsin inhibitors [70,71], vasodilating agents [72][73][74] and surfactant substitutes [75][76][77][78].…”
Section: Paas That Enhance Efficiency Of Lung Ventilation and Gas Excmentioning
confidence: 99%
“…Infasurf ® (calfactant) Intratracheal Suspension is a sterile, non-pyrogenic lung surfactant intended for intratracheal instillation. It is an extract of natural surfactant from calf lungs, which includes phospholipids, neutral lipids, and hydrophobic surfactant-associated proteins B and C. Other examples of artificial surfactant are presented in [75][76][77][78]. …”
Section: Paas That Enhance Efficiency Of Lung Ventilation and Gas Excmentioning
confidence: 99%